PHYTOCHEMICAL TEST OF MANGROVE Avicennia alba, Rhizopora apiculata AND Sonneratia alba FROM MUSI RIVER ESTUARY, SOUTH SUMATERA - Rahmania, Nadya; Herpandi, Herpandi; Rozirwan, Rozirwan (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2018)
Mangrove is one of the plants that has the potential to be developed into medicinal plants. However, further research is needed to prove scientifically the content of secondary metabolites in it. This study aims to identify the secondary metabolites contained from leaves and roots in Avicennia alba, Rhizopora apiculata and Sonneratia alba. The leaves and roots of mangroves extracted by maceration using ethyl acetate. The secondary metabolites contained in mangrove samples obtained by doing phytochemical tests through color tests. Phytochemical test results showed that secondary metabolites contained in mangrove Avicennia alba are flavonoids, steroids/triterpenoids, saponins, and tannins/phenols in leaf samples, whereas in its root samples it contains flavonoids and steroids/triterponoid compounds. Sonneratia alba contains flavonoids, steroids/teriterpenoids, saponins and tannins/phenols in its leaf samples, while the root samples contain flavonoids, steroids/teriterpenoids and tannins/phenols compounds. The leaf samples of mangrove Rhizopora apiculatacontains flavonoid and steroid/triterpenoid compounds whereas in its root samples contains flavonoids, steroids/triterpenoids, saponins as well as tannins/phenols.